CONTROL OF FUEL CELL/BATTERY SOURCE FOR ELECTRIC VEHICLES - Bilhan, Ayşe Kocalmış; Çalışkan, Abuzer (Zülküf GÜLSÜN [EN], 2018)
Fuel cells are considering as primary power source for portable applications, electrical vehicles and residential applications in the future. However, since the voltage value obtained from a single fuel cell is too low, the output voltage values of the fuel cells must be increased. Therefore, DC/DC and DC/AC converters should be used to obtain a balanced output voltage and to make FCs available for all applications. This paper discusses the principle and electrical characteristics of the fuel cell, DC/DC boost converter and DC/AC inverter.